Luteolin and Vernodalol as Bioactive Compounds of Leaf and Root Vernonia amygdalina Extracts: Effects on α-Glucosidase, Glycation, ROS, Cell Viability, and In Silico ADMET Parameters - Francine Medjiofack Djeujo; Valentina Stablum; Elisa Pangrazzi; Eugenio Ragazzi; Guglielmina Froldi (MDPI AG, 2023)
The aqueous decoctions of Vernonia amygdalina (VA) leaves and roots are widely used in traditional African medicine as an antidiabetic remedy. The amount of luteolin and vernodalol in leaf and root extracts was detected, and their role was studied regarding α-glucosidase activity, bovine serum albumin glycation (BSA), reactive oxygen species (ROS) formation, and cell viability, together with in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties. Vernodalol did not affect α-glucosidase activity, whereas luteolin did. Furthermore, luteolin inhibited the formation of advanced glycation end products (AGEs) in a concentration-dependent manner, whereas vernodalol did not reduce it. Additionally, luteolin exhibited high antiradical activity, while vernodalol demonstrated a lower scavenger effect, although similar to that of ascorbic acid. Both luteolin and vernodalol inhibited HT-29 cell viability, showing a half-maximum inhibitory concentration (IC50) of 22.2 µM (−Log IC50 = 4.65 ± 0.05) and 5.7 µM (−Log IC50 = 5.24 ± 0.16), respectively. Finally, an in silico ADMET study showed that both compounds are suitable candidates as drugs, with appropriate pharmacokinetics. This research underlines for the first time the greater presence of vernodalol in VA roots compared to leaves, while luteolin is prevalent in the latter, suggesting that the former could be used as a natural source of vernodalol. Consequently, root extracts could be proposed for vernodalol-dependent antiproliferative activity, while leaf extracts could be suggested for luteolin-dependent effects, such as antioxidant and antidiabetic effects.